System for real time support in construction materials selection - Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras; Banaitis, Audrius; Trinkūnas, Vaidotas (International Journal of Strategic Property Management, 2010)
The significant part of the constructions’ value consists of construction materials price. With the aim of using financial resources for the construction effectively, it is very important that well considered and reasonable decisions should be made regarding the selection of construction materials. Most of all construction on‐line systems seek to find how to make the most economic construction decisions and essentially these decisions are intended only for economic objectives. Construction alternatives that are under evaluation have to be evaluated not only from the economic position, but also take into consideration qualitative, technical, technological and other characteristics. Additionally, in seeking to facilitate the work of decision‐makers, computer technologies are used that operates according to particular models. These models are based on special mathematical methods in order to facilitate decision‐making and apply to a certain decision area. In this article, the possibilities of applying methods for popular decision‐making are analyzed regarding the selection of construction materials.First Published online: 18 Oct 2010